Vulnerability in the area of the "Machería" before the union of the beaches "Brava" and "Mansa" in the district of Lomas, Caravelí, Arequipa - Nuñez Saire, Miguel Humberto (2022)
The purpose of this research work is to raise awareness of the high vulnerability to the possible union, as happened years ago, of the beach known as the "Brava" and "Mansa" in the area known as the “Machería” in the district of Lomas, Caravelí, Arequipa. Also make known the reason why they build their homes in an area of high vulnerability to an imminent tsunami since we are in the Pacific Ring of Fire and this makes there a greater vulnerability to an earthquake and its subsequent formation of the tsunami. We will include several aspects of Physical Geography, as well as the factors of vulnerability that can be seen in the study area.